Implementasi A/B Testing sebagai peningkatan pengalaman pengguna pada aplikasi masterfish diukur dengan Conversion Rate (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
In this Current technological developments, especially technology in the service sector, which is engaged in helping MSME communities whose system needs are becoming increasingly complex, can be seen from the widespread use and development of multi-sector information systems such as information management systems in villages or government as well as those engaged in the health sector. In 2022, most of them will start using a mobile-based system that can be accessed anywhere. With such a system, its use will be more efficient and flexible. However, to achieve an interface design that is friendly and acceptable to the user, validation is needed to determine whether the design that has been made has met the criteria required by the user. Sometimes the first design that is made does not necessarily meet the desired criteria. Therefore, we need an approach in the form of A/B testing where this is a method of comparison between design 1 and design 2, which is seen to be better in terms of usability level. This method was chosen to ensure that every existing assumption can be validated, whether or not it is true. Every time you optimize your designs, apart from being made for automation, a/b testing is usually used to help entities understand what users or the market want.